Islam dan Perkembangan Bahasa Melayu - Ening Herniti (Jurnal Lektur Keagamaan, 2017)
The spread of Islam in Nusantara has not only influenced social change, but also in language development. One of the languages used in Nusantara at that time was the Malay language. Malay as lingua franca has an important role in communication between traders in the Malacca Strait. Arabic also serves as a lingua franca especially in the spread of Islam. Arabic and Malay have the same position, namely as lingua franca, causing language contact. This language contact represents a balance of two languages resulting in language borrowing. This research is libraryresearch with qualitative-descriptive method. This paper describes the influence of the spread of Islam in Nusantara to the development of Malay (Bahasa). The conclusion of this study shows that the spread of Islam in Nusantara influences the system alphabet (alphabet Jawi), the form of loanword, the domain of loanword, and Arabic-Latin transli¬teration. Keywords: The spread of Islam; influence; contact language; lingua franca; loanword Penyebaran agama Islam di Nusantara tidak hanya berpengaruh pada perubahan sosial, tetapi juga pada perkembangan bahasa. Salah satu bahasa yang digunakan di wilayah Nusantara pada saat itu adalah bahasa Melayu, yang kemudian menjadi bahasa Indonesia. Bahasa Melayu sebagai lingua franca memiliki peranan penting dalam memperlancar komunikasi antarpedagang di Selat Malaka. Bahasa Arab juga berperan sebagai lingua franca terutama dalam penyebaran agama Islam. Bahasa Arab dan bahasa Melayu memiliki kedudukan yang sama, yakni sebagai lingua franca sehingga menimbulkan kontak bahasa. Peristiwa kontak bahasa ini mepresentasikan adanya keseimbangan dua bahasa yang mengakibatkan peminjaman bahasa. Penelitian ini adalah penelitian pustaka dengan metode deskriptif-kualitatif. Tulisan ini memaparkan pengaruh penyebaran Islam di Nusantara terhadap perkembangan bahasa Melayu (bahasa Indonesia). Hasil penelitian ini menunjukkan bahwa penyebaran agama Islam di Nusantara berpengaruh pada sistem aksara (abjad Jawi), bentuk serapan, bidang penyerapan, dan transliterasi Arab-Latin. Kata Kunci: penyebaran agama Islam; pengaruh; kontak bahasa; lingua franca; serapan